Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2174/1871526515666150731113305
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of combined therapy with Deferiprone and Silymarin as iron chelators in Egyptian Children with Beta Thalassemia major

Abstract: 'Extensive multicenter studies in large number of patients with longer follow up period and more advanced methods of assessment of iron status to clarify the exact role of silymarin in reduction of iron over load in thalassemic children'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…At higher dosages (>1,500 mg/day), silymarin may have gastrointestinal and laxative effects (Luper, ). We utilised silymarin to a total dose of 420 mg, split into three separate doses, similar to several previous studies for evaluation of the iron‐chelating effects in thalassemia patients (Gharagozloo et al, ; A. Hagag, ; Moayedi et al, ). However, we did not assess adherence and compliance to silymarin/placebo in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At higher dosages (>1,500 mg/day), silymarin may have gastrointestinal and laxative effects (Luper, ). We utilised silymarin to a total dose of 420 mg, split into three separate doses, similar to several previous studies for evaluation of the iron‐chelating effects in thalassemia patients (Gharagozloo et al, ; A. Hagag, ; Moayedi et al, ). However, we did not assess adherence and compliance to silymarin/placebo in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Effective iron chelation remains one of the vital objectives of clinical management of transfusion‐dependent thalassemia, and recent studies have focused on the use of natural iron chelators (Gharagozloo et al, ; A. Hagag, ; Moayedi et al, ). Safe and effective oral chelators as adjuvants to standard iron chelators are required for transfusion‐dependent thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one research on patients with beta thalassemia, oral administration of 140‐mg silymarin three times daily for 6 months in combination with deferiprone (20‐40 mg/kg/day) was without any toxicity. Silymarin also showed iron‐chelating activity, and after the termination of treatment, the level of ferritin and iron were diminished, but no significant changes were observed in serum creatinine, alanine aminotransferase, and aspartate aminotransferase (Hagag, Elfaragy, Elrifaey, & Abd El‐Lateef, ). In another study on patients, they treated with subcutaneous desferrioxamine and oral 140‐mg silymarin three times in a day for 9 months.…”
Section: Safety and Adverse Reactions Of Oral Silymarin In Humansmentioning
confidence: 99%
“…Earlier studies observed an additional, positive effect (e.g. reduced serum iron and serum ferritin in 3 out of 4 trials) for silymarin [125,126]. In addition, the role of silymarin in a combined regimen with deferasirox or deferiprone in the treatment of the iron overload in Beta-Thalassemia is currently under investigation in several clinical trials.…”
Section: Iron Overloadmentioning
confidence: 99%